A low metallicity massive contact binary star system candidate in WLM identified by Hubble and James Webb space telescope imaging - Gull, Maude; Weisz, Daniel R.; El-Badry, Kareem; Henneco, Jan; Savino, Alessandro; Durbin, Meredith; Choi, Yumi; Cohen, Roger E.; Cole, Andrew A.; Correnti, Matteo; Dalcanton, Julianne J.; Gilbert, Karoline M.; et al. (The astrophysical journal, 2025)
We present archival Hubble Space Telescope (HST) and JWST ultraviolet through near-infrared time series photometric observations of a massive minimal-contact binary candidate in the metal-poor galaxy Wolf-Lundmark-Melotte (Z = 0.14Z⊙). This discovery marks the lowest metallicity contact binary candidate observed to date. We determine the nature of the two stars in the binary by using the eclipsing binary modeling software PHysics Of Eclipsing BinariEs (PHOEBE) to train a neural network to fit our observed panchromatic multiepoch photometry. The best-fit model consists of two hot main-sequence stars ( K, M⊙, and K, M⊙). We discuss plausible evolutionary paths for the system, and suggest the system is likely to be currently in a contact phase. Future spectroscopy will help to further narrow down evolutionary pathways. This work showcases a novel use of data of JWST and HST imaging originally taken to characterize RR Lyrae. We expect time series imaging from LSST, BlackGEM, etc. to uncover similar types of objects in nearby galaxies.